The defective copy theory of movement : evidence from wh-constructions in Cape Verdean Creole - Alexandre, Nélia (Creole language library, 2012)
Within the framework of Chomsky's Principles and Parameters Theory and the Minimalist Program, this work presents a detailed discussion of the different types of wh-question formation and relativization strategies in Cape Verdean Creole (Santiago variety), especially focusing on wh-movement of PPs. The book explores the Copy Theory of Movement, discussing a defective copy construction involving wh-movement of PPs which poses interesting theoretical questions as to how the defective copy is to be generated and form a chain with the relevant displaced wh-constituent. It is also shown that the de.